Impact of immature platelet fraction on platelet reactivity during prasugrel maintenance treatment - Monica Verdoia; Patrizia Pergolini; Roberta Rolla; Harry Suryapranata; Elvin Kedhi; Giuseppe De Luca (Platelets, 2019)
Residual high on-treatment platelet reactivity (HTPR) despite dual antiplatelet therapy (DAPT) has emerged as a predictor of major ischemic events in patients undergoing percutaneous coronary interventions (PCIs), especially after an acute cardiovascular event. However, its determinants are still poorly defined. Therefore, the aim of the present study was to evaluate the role of the percentage of reticulated platelets on HTPR in patients on DAPT with ASA (100–160 mg) and prasugrel (10 mg). Platelet reactivity and the reticulated platelets fraction (immature platelets fraction [IPF]) were assessed at 30–90 days after an acute coronary syndrome. Aggregation was assessed by multiple-electrode aggregometry. HTPR was defined as ADP test > 417 AU × min. Our population is represented by 180 ACS patients undergoing stent implantation, divided according to median values of IPF (< or ≥ 2.8%). Higher IPF values were associated to lower platelet count (p < 0.001) and a higher rate of active smokers (p = 0.02). No difference was observed in terms of mean platelet reactivity, with different activating stimuli. The prevalence of HTPR on prasugrel did not significantly differ in patients with IPF < or ≥ 2.8% (8%vs. 11.8%, p = 0.46; adjusted OR [95% CI] = 1.89 [0.66–5.4], p = 0.24). Our study showed that in patients treated with prasugrel after PCI for ACS, the immature platelet fraction influences neither platelet reactivity nor the rate of HTPR.